Outsourcing Marketing Plans for Small and Medium Enterprises using Knowledge Sharing Process Case study: Tehran Wood and Furniture Companies - Yaser Hosseini; Hamed Fazlollahtabar; Minoo Talebi Ashoori (International Journal of Industrial Engineering and Production Research, 2021)
This study proposes an outsourcing mechanism for marketing plans in small and medium-sized enterprises (SMEs) using knowledge sharing.  SMEs may not be able to establish a marketing department due to operational expenditures. Therefore, organizing a marketing agency to handle marketing concerns of SMEs is significant. First, SMEs are clustered regarding their activity area, products, services, and etc. Then, for SMEs in a same cluster, the marketing agency should collect the required information to process marketing actions. The challenge is how to gather and deposit information in common among SMEs in a cluster. Knowledge sharing is one of the stages of knowledge management helping to distribute information among elements of a system. Thus, the process of knowledge sharing is investigated in outsourcing marketing activities. Accordingly, a questionnaire was prepared based on research hypotheses. After confirmation of validity and reliability, the questionnaire was given to managers and employees of furniture companies in Tehran province, Iran. The collected questionnaires were analyzed using SPSS software version 24.0.  According to the statistical sample of the research, descriptive statistics, and inferential statistics were analyzed. Descriptive statistics were used to describe the demographic characteristics of respondents. The inferential statistics, Kolmogorov-Smirnov test was used first for the test of normality of data. Considering normality of the data, T-student test was used to obtain the relationship between variables. Finally, the results of the research showed that there is a positive and significant relationship between outsourcing marketing in SMEs using knowledge sharing. Therefore, it is suggested that SMEs pay particular attention to outsourcing their marketing activities using knowledge sharing.